“The Fatal Series” by V. Bryusov and the Problems of Sonnets Corona Poetics - HAKOBYAN, LEVON (Bulletin of Yerevan University H: Russian Philology, 2021)
The paper is devoted to the study of "The Fatal Series" by V. Bryusov in the context of the sonnets corona theory. The crown of sonnets is regarded as a supertextual level phenomenon, and the problems of the cross-textual relations between the master sonnet and the main corpus as well as between the main corpus texts are considered. Two types of cross-textual links (obligatory and complementary) and their function in the context of “The Fatal Series” are revealed.